A study on the effect of normal saline And dextrose saline solution infusion During labour: a comparative study - Ernie Haryantle, Shaharudin (2010)
To evaluate the effects of intrapartum 0.9% Nonnal Saline infusion and Dextrose Saline solution on the fetal and maternal outcome. A prospective controlled study in which low risk nullipara with singletons in active labour at tenn were randomized to receive intravenously either Nonnal Saline or Dextrose Saline as the maintenance fluid during active labour. Antepartum and intrapartum factors were recorded. Maternal and neonatal outcomes were analyzed. Of 400 subjects enrolled, 395 met inclusion criteria and completed the study. There were no statistical differences between the two groups regarding maternal age, maternal weight on admission and gestational age. The difference in second stage duration was also not significant. Newborn birth weight, gender, incidence of meconium and Apgar scores were not statistically different. The difference in the median of labour length between the Nonnal Saline and Dextrose Saline was statistically significant (340 ± 112 min vs 300 ± 110 min; p=0.04). There were significant differences between the Nonnal Saline group and Dextrose Saline group in cord blood pH values (7.25 ± 0.04 vs. 7.28 ± 0.04; p=O.OOl), PCDl values (45.38 ± 4.13mmHg vs 41.05 ± 4.68 mmHg; p=O.OOl) and base excess (-6.2 ± 1.2 mmo11L vs. -4.5 ± 1.4 mmol/L;p=O.OOI). Administration of a Dextrose Saline solution was associated with lower incidence of umbilical cord acidemia, reduced the need for augmentation and shortened the labour duration in term nullipara subjects in active labour.